How to Develop and Implement a Computerized Decision Support System Integrated for Antimicrobial Stewardship? Experiences From Two Swiss Hospital Systems - Catho, Gaud; Centemero, Nicolo S.; Waldispühl Suter, Brigitte; Vernaz, Nathalie; Portela, Javier; Da Silva, Serge; Valotti, Roberta; Coray, Valentina; Pagnamenta, Francesco; Ranzani, Alice; Piuz, Marie-Françoise; Elzi, Luigia; et al. (Frontiers in Digital Health, 2021)
Background: Computerized decision support systems (CDSS) provide new opportunities for automating antimicrobial stewardship (AMS) interventions and integrating them in routine healthcare. In the context of the COMPuterized Antibiotic Stewardship Study (COMPASS), we developed and implemented two CDSSs for antimicrobial prescriptions integrated into the in-house electronic health records of two public hospitals in Switzerland. In this narrative review we describe key lessons learned when developing and implementing such systems. Recommendations: During the development stage, start by drafting the CDSS as an algorithm and use a standardized format to communicate the desired functionalities of the tool to all stakeholders. Set up a multidisciplinary team bringing together Information Technologies (IT) specialists with development expertise, clinicians familiar with “real-life” processes in the wards and if possible, involve collaborators having knowledge in both areas. When designing the CDSS, make the underlying decision-making process transparent for physicians and be sure to find the right balance between force and persuasion to ensure adoption by end-users. It is also key to correctly assess the clinical and economic impact of your tool, therefore use standardized terminologies and limit the use of free text for analysis purpose. At the implementation stage, plan usability testing early, develop an appropriate training plan suitable to end users’ skills and time-constraints and think ahead of additional challenges related to the study design that may occur. Finally, during the assessment and adaptation stages plan ahead maintenance, adaptation and related financial challenges and stay connected with institutional partners to leverage potential synergies with other informatics projects.